Improve Students Learning Achievement in Narrative Text of English Subject through the Implementation of Problem-Based Learning - Dewi, Suarni; Munir, Munir; Nurbaena, Nurbaena (Universitas Negeri Makassar, 2024)
Abstract. This Classroom Action Research (CAR) is motivated by the low learning autcomes of students in the subject of English, particulary in the area of Narrative Text. This is due to the conventional teaching approach, which is more teacher –centered. The aim of this Classroom Action Research (CAR) is to improve the students activity and learning aoutcomes in English language learning, spesifically in the area of narrative text, in class X.5 at SMAN 3 Bantaeng through the implementation od Problem Based-Learning (PBL). The benefit of this Classroom Action Research (CAR) is contribute ideas for transforming teaching from a teacher-centered approach to a student-centered approach through the application of Problem Based Learning (PBL). Consequently, students will be actively involved in searching, discovering, and acquiring knowledge on their own. This classroom Action research (CAR) consist of two cycle. Data for this research were collected from both teachers (observers) and students through observations, test, and documentation. Based on the research data from cycle I to cycle II, it is evident that both the students activity and their learning outcomes in the learning process, through the implementation of Problem Based_learning (PBL), have significantly improved compared to the previous lecture-based method . In conclution, the application of Problem Based-Learning (PBL) can improve the students activity and learning outcomes in English language learning, specifically in the area of Narrative Text, in class X.5 at SMAN 3 Bantaeng. Keywords: problem based-learning, students achievement, narrative text